Language consulting and language management from the perspective of the Hungarian Language Consulting Service - Ludányi, Zsófia; Domonkosi, Ágnes (Taikomoji kalbotyra, 2023)
Applying the framework of Language Management Theory, the paper explores how language consulting services may be involved in the management of various language problems experienced by speakers. Focusing on the discourse-shaping activity of everyday speakers, Language Management Theory is a comprehensive theoretical framework aimed at the detection, analysis and treatment of linguistic and communicative problems. One viable path toward solving language problems is for language users to contact a language consulting service. The paper shows how the Language Consulting Service of the HUN-REN Hungarian Research Centre for Linguistics applies problem-management practices to the spelling and language use problems of inquirers. The practice of institutional language consulting provides a bridge between simple and organised language management processes, and between the micro and macro levels of management. In today’s complex linguistic context, which promotes linguistic diversity, the role of language consulting services is primarily to provide a data-driven and discursive approach to language problems, working closely with the language users themselves.
Keywords: language management; Language Consulting Service; Hungarian; language problems and solutions; spelling problems; correctness